Pengaruh Profitabilitas, Kepemilikan Asing, Kepemilikan Manajemen, dan Leverage Pada Intensitas Pengungkapan Corporate Social Responsibility - Wulandari, Anak Agung Ayu Intan; Sudana, I Putu (E-Jurnal Akuntansi; Vol 22 No 2 (2018), 2018)
Corporate Social Responsibility (CSR) is the business world's commitment to act ethically and contribute to the economic development of local communities and the wider community. This study aims to obtain empirical evidence of the influence of profitability, foreign ownership, ownership management, and leverage on the intensity of Corporate Social Responsibility disclosure. This research is conducted on mining companies listed in Indonesia Stock Exchange period 2013-2016. The number of samples is 32 observations, with nonprobability sampling method and data collection method of documentation. Data analysis technique of this research is multiple linear regression analysis. This study concludes that profitability has no effect on CSR disclosure intensity, foreign ownership has no effect on CSR disclosure intensity, management ownership has positive effect on CSR disclosure intensity, and leverage has negative effect on CSR disclosure intensity. The results provide the basis for management in taking disclosure policy of CSR intensity. Keywords: Profitability, foreign ownership, management ownership, leverage, intensity of corporate social responsibility disclosure